Kasus Anak Sebagai Pelaku Tindak Pidana Pencurian Berdasarkan Kajian Kriminologi - Syahbana, Ikrima Salsa; Pura, Margo Hadi (Peneliti.net, 2024)
The latest issue faced is not limited to theft; nowadays, theft is a prevalent concern, involving not only adults but also children and teenagers. The root cause of juvenile theft lies in deviant mindsets fostered by their surroundings. Addressing criminal acts by children becomes a legal challenge for the state, and Indonesia, as a legal state, governs such events through the Republic of Indonesia Law no. 11 of 2012, focusing on Juvenile Justice. This study endeavors to identify the criminal sanctions imposed on children involved in theft. Employing sociological legal research with empirical properties, the approach entails descriptive analysis. Primary and secondary data sources are utilized, gathered through literature study. Descriptive observation is employed for analysis, revealing that children's inclination towards theft stems from environmental, social, and economic factors, coupled with insufficient parental supervision during their formative years.